Absence of a continuous water spray system does not influence the microbiological contamination of the conveyor belts in chicken slaughterhouses - Soares, Vanessa Mendonca [UNESP]; Viana, Cibeli; Pereira, Juliano Goncalves [UNESP]; Destro, Maria Teresa; Nero, Luis Augusto; Bersot, Luciano dos Santos; Almeida Nogueira Pinto, Jose Paes de [UNESP] (Elsevier B.V., 2018)
The objective was to evaluate whether the absence of a water spray affects the microbial contamination on chicken conveyor belts in slaughterhouse. A total of 1280 samples from modular and smooth conveyor belts, with and without water spray, were evaluated in four slaughterhouses in Brazil. Superficial swabs of conveyor belts were performed at the indicated time periods (T-0 - 5:00 am; T-1 - 9:00 a.m; T-2 - 5:00 p.m.; and T-3 - 10:00 p.m.) and submitted to counting of mesophiles, Enterobacteriaceae, coliforms, and E. coli. The data were evaluated by measuring the increment (positive or negative) in contamination between the periods and comparing the means of the conveyor belts with and without water spray. On the modular conveyor belts, the absence of water spray allowed for a significant increase in the counts only in the T-2-T-3 interval for coliforms and E. soli. On the smooth conveyor belts, the absence of water spray allowed for a significant increase in Enterobacteriaceae counts only in the T-2-T-3 interval. At the other intervals, absence in the water had no influence on the indicator counts. These results demonstrated that the use of a water spray system on conveyor belts does not influence the contamination count.
Keywords: Chicken; Conveyor belts; Contamination; Cleaning; Slaughter